Challenges facing human resources management in applying modern concepts of human resources management – An applied study on private hospitals in Khamis Mushait – - Alshahrani, Bader Yahya; Alammar, Adullah Ali (Journal of Economic, Administrative and Legal Sciences, 2021)
A study entitled the challenges facing human resource management in applying the modern concepts of human resources management by applying to the hospitals in Khamis Mushait. This study aims to identify the challenges facing human resource management in applying modern concepts of human resources management. In order to achieve the objectives of the study, of the nature of the study, while the questionnaire was used as a main tool for data collection. The study population is from the private hospitals in Khamis Mushait. The sample of the study was 91 workers. The study reached a set of results. Maha: The challenges of the external environment are the most influential in the application of modern concepts of human resources management in the hospitals of Khamis Mushait, while the application of modern concepts of human resources management in private hospitals in Khamis Mushait medium degree with a relative weight (65.80%). The results showed no differences Statistical significance among the opinions of hospital staff in Khamis Mushait on their appreciation of the challenges facing human resource management in applying the modern concepts of human resources management due to the gender variable and the variable age, the variable of scientific qualification and the variable years of service. To study the need to apply modern concepts of human resources management as an essential part of the culture of the institution, and to create a permanent relationship between management and employees to promote the application of modern concepts of human resources management, and attention to continuous training to develop the skills of staff and develop their abilities to achieve development of the hospital.